2015
DOI: 10.1002/ejoc.201501112
|View full text |Cite
|
Sign up to set email alerts
|

Carbocation Catalysis: Oxa‐Diels–Alder Reactions of Unactivated Aldehydes and Simple Dienes

Abstract: The versatility of the trityl cation (TrBF4) as a highly efficient Lewis acid organocatalyst is demonstrated in the oxa‐Diels–Alder reaction of various unactivated aromatic and aliphatic aldehydes and simple unactivated dienes, such as isoprene and 2,3‐dimethylbutadiene. The transformation proceeds smoothly to give 3,6‐dihydropyrane adducts in high to moderate yields with catalyst loadings down to 1.0 mol‐% under mild reaction conditions. In contrast to most previously reported strategies, this protocol does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…To evaluate the catalytic performance of PCN-625(Fe), we compared its activity with those of other reported catalysts for the cycloaddition between 1c and 2a (Table S11). It was found that PCN-625(Fe) exhibited a performance superior to those of the reported UNLPF-16-Fe III , 52 FeP p−H -HCP, 53 TrBF 4 , 54 [Fe(TPP)]BF 4 , 51,55 Sc-(OPf) 3 , 56 and AlCl 3 , 57 which required higher amounts of catalysts or longer reaction time but afforded lower yields. Meanwhile, due to their similar skeletal structures, its catalytic performance was almost the same as that of PCN-223(Fe).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…To evaluate the catalytic performance of PCN-625(Fe), we compared its activity with those of other reported catalysts for the cycloaddition between 1c and 2a (Table S11). It was found that PCN-625(Fe) exhibited a performance superior to those of the reported UNLPF-16-Fe III , 52 FeP p−H -HCP, 53 TrBF 4 , 54 [Fe(TPP)]BF 4 , 51,55 Sc-(OPf) 3 , 56 and AlCl 3 , 57 which required higher amounts of catalysts or longer reaction time but afforded lower yields. Meanwhile, due to their similar skeletal structures, its catalytic performance was almost the same as that of PCN-223(Fe).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Cancer is a well-recognized disease with a multifactorial nature that is known for uncontrolled cell growth and abnormal cell spread as well. It is ranked to be the second cause of death all over the world. , Nowadays, there are various techniques to fight cancer such as chemotherapy, radiotherapy, and/or surgery. The epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase (RTK) that is involved in the development and homeostasis of epithelial tissues. Moreover, the family of EGFR has a vital role in cell signaling through overexpression which is linked to the progress of various human solid malignancies, especially breast cancers and non-small-cell lung cancers. The use of EGFR inhibitors to block EGFR-mediated signaling pathways is a common approach for the treatment of several malignancies. There are three generations of EGFR-tyrosine kinase inhibitors available: the first one includes reversible EGFR inhibitors (erlotinib and gefitinib); the second generation includes irreversible EGFR blockers (afatinib and dacomitinib); and the third one includes a wild-type-sparing, irreversible EGFR inhibitor (osimertinib). The fourth generation inhibitors (which include EAI04518 and other non-covalent inhibitors) are now in preclinical testing. , In addition, the EGFR is well established as a biomarker in the case of resistant cancers, as its secondary mutations have been observed to occur under treatment components …”
Section: Introductionmentioning
confidence: 99%
“… 11 14 Moreover, the family of EGFR has a vital role in cell signaling through overexpression which is linked to the progress of various human solid malignancies, especially breast cancers and non-small-cell lung cancers. 15 18 The use of EGFR inhibitors to block EGFR-mediated signaling pathways is a common approach for the treatment of several malignancies. 17 19 There are three generations of EGFR-tyrosine kinase inhibitors available: the first one includes reversible EGFR inhibitors (erlotinib and gefitinib); the second generation includes irreversible EGFR blockers (afatinib and dacomitinib); and the third one includes a wild-type-sparing, irreversible EGFR inhibitor (osimertinib).…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatoms at the β-position of the aryl aldehydes can greatly promote the reactivity of the substrates. Franzen and co-workers reported a carbocation-catalyzed ODA reaction . The possible role of counteranions toward the efficiency of this reaction and spectroscopic insights of the reaction has yet not been explored.…”
Section: Introductionmentioning
confidence: 99%